Hippocampal Laminar Distribution of Tau Relates to Alzheimer's Disease and Age of Onset - Seifan, Alon (J Alzheimers Dis, 2015)
BACKGROUND: Cerebral deposition of phospho-tau in Alzheimer's disease (AD) occurs with varying patterns within hippocampus. Lamina-specific tau changes in AD may reflect trans-synaptic propagation of phospho-tau along neuroanatomical pathways. OBJECTIVE: To study patterns of tau deposition within inner (IML) and outer (OML) molecular layers of dentate gyrus and their clinical and neuropathological correlates. METHODS: 98 consecutive autopsied brains from the Columbia University Brain Bank were stained for phospho-tau using AT-8. Staining density was rated as High versus Low within IML and OML. Four patterns were observed among the 98 brains: High IML&OML, n = 44; High OML Only (n = 35); High IML Only (n = 5); and Low IML&OML (n = 14). Demographic, clinical, and neuropathological characteristics of these four groups were compared. RESULTS: High IML&OML subjects, versus High OML Only, were more likely to fulfill CERAD criteria for Definite AD (93% versus 66%, p < 0.01) and to have higher median Braak stage (6 versus 5, p < 0.01) and earlier mean age of onset (65.9 versus 73.7 y, p = 0.02), with similar symptom duration. Using logistic regression, the association between High IML&OML and AD remained significant after adjustment for demographics but not symptom duration. In the 70 subjects with Definite AD, High IML&OML was associated with younger age of onset (mean difference 3.7 years, 95%CI −6.7 to −0.7, p < 0.01), after adjustment for demographics and symptom duration. CONCLUSIONS: Phospho-tau pathology, when prominent within both IML and OML, is associated with CERAD diagnosis of Definite AD and earlier age of onset in AD. Laminar patterns of tau deposition reflect regional involvements during disease course.